Implantes dentais curtos: alternativa conservadora na reabilitação bucal - Santiago Júnior, Joel Ferreira [UNESP]; Verri, Fellippo Ramos [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Moraes, Sandra Lúcia Dantas de [UNESP]; Carvalho, Bruno Machado de [UNESP] (My University, 2010)
The short dental implants represent an option of previsible treatment, its main indication lives in the possibility of avoiding techniques surgical invasive. The literature in the display that the geometry of the implants is of vital importance, combined with wide diameters and surface treatment, mainly when the bone quality is unfavorable. The mechanical resistance can be enlarged, increasing the number of implants and being used the spliting among them. A rigorous protocol prosthodontist should be following with intention of to avoid oblique loads and to control habits parafuncionais. We aimed at to discuss, through a wide bibliographical revision the short dental implants, their characteristics and indications, giving emphasis to the aspects biomechanic of the same ones. Material and Method: The bases given: Pubmed, ISI and Dentistry Oral Science from 1990 to 2009, were consulted to identify researches related to the length of the dental implants, with emphasis to the considered short and the biomechanics related to the same ones. They were located 568 articles, being selected 69 that gathered the inclusion criteria. Result: Among these 69 selected, 26 articles agreed the evidence level. Conclusion: Inside of the limits of appraised data, it can be concluded that the short implants represent a good treatment alternative, especially for cases with reduced bone bed. However a rigorous indication protocol and use should be followed for warranty of the success of the treatment.

Os implantes dentários curtos representam uma opção de tratamento previsível, e sua principal indicação reside na possibilidade de evitar técnicas cirúrgicas invasivas. A literatura nos mostra que a geometria dos implantes é de vital importância, combinada com largos diâmetros e tratamento de superfície, principalmente quando a qualidade óssea é desfavorável. A resistência mecânica pode ser ampliada, aumentando-se o número de implantes e usando-se a esplintagem entre eles. Um rigoroso protocolo protético deve ser seguido com o intuito de evitar cargas oblíquas e controlar hábitos parafuncionais. Objetivamos discutir, através de uma revisão bibliográfica ampla os implantes dentários curtos, suas características e indicações, dando ênfase aos aspectos biomecânicos destes. Material e Método: As bases dados: Pubmed, ISI e Dentistry Oral Science de 1990 a 2009, foram consultadas para identificar pesquisas relacionadas ao comprimento dos implantes dentários, com ênfase aos considerados curtos e à biomecânica relacionada a estes. Foram localizados 568 artigos, sendo selecionados 69 que reuniram os critérios de inclusão. Resultado: Dentre esses 69 selecionados, 26 artigos estavam de acordo com o nível de evidência. Conclusão: Dentro dos limites de dados avaliados, pode-se concluir que os implantes curtos representam uma boa alternativa de tratamento, especialmente para casos com leito ósseo reduzido. Porém um rigoroso protocolo de indicação e uso deve ser seguido para a garantia do sucesso do tratamento.
Short dental implants: alternative conservative in the oral rehabilitation
Keywords: Dental implant; Biomechanics; Risk factors; Implantes dentários; Biomecânica; Reabilitação bucal